Association between Albuminuria and Serum Phosphate Levels in Non-Dialysis Stage 3-5 Chronic Kidney Disease Patients - Atika; Harfonso, Ernesto Everald Baibelino; Mardiana, Nunuk (Current Internal Medicine Research and Practice Surabaya Journal, 2023)
Introduction: Chronic kidney disease (CKD) remains a global burden and catastrophic disease as about 697.5 million people suffering from it in 2017. About 42% of CKD mortality in Indonesia is related to cardiovascular complications. Hyperphosphatemia, a manifestation of chronic kidney disease-mineral bone disorder, could increase the risk of cardiovascular mortality. Albuminuria has been proven to inhibit the compensatory mechanisms for hyperphosphatemia, thereby aggravating this condition. This study was conducted to analyze the association between albuminuria and serum phosphate levels among CKD patients in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia.Methods: This cross-sectional study used medical records of 129 non-dialysis stage 3-5 CKD patients at the outpatient clinic of Dr. Soetomo General Academic Hospital from March-November 2021. Descriptive analysis was performed on albuminuria, serum phosphate, age, sex, body mass index, comorbid, blood chemistry tests, and CKD stages data. Correlational analysis was conducted using the Spearman Rank test on albuminuria and serum phosphate levels.Results: The majority of the subjects in this study were male (55.81%); mean age was 55.21±11.99 years; mean BMI was 22.39±2.27 kg/m2; hypertension was found in 65.89% of the patients; mean eGFR was 25.01±16.1 ml/min/1.73 m2 and dominated by CKD stage 3-5. The distribution of albuminuria grade was dominated by heavy albuminuria (>300 mg/g) and the mean serum phosphate level was 4.81±1.9 mg/dl. Spearman Rank analysis found a significant positive correlation with weak association strength (p<0.001; rs=0.277) between albuminuria and serum phosphate levels.Conclusion: There was a significant positive correlation with weak association strength between albuminuria and serum phosphate levels.